O papel do orientador: o processo de orientação no curso de pós-graduação em Biblioteconomia da UFMG - Madalena Martins Lopes Naves (1993)
The evolution of the graduate courses in Brazil and the first master courses in Library Science and Information Science were taken as a theoretical basis for the study of the thesis counselling process. Reserach in those areas is not yet consolidated and its development began after the creation of the first master courses during the 1970/s. The majority of the master students have no prior experience in research before being egaged in their theses. This is the main reason for the emphasis given on the advisotr´s role during this process. the iformation transfer that occurs between advisors and students produces knowledge and contributes to the Library an Information Science at the Universidade Federal de Minas Gerais, froem 1976 an 1990, shows quantitative and qualitative data, including opinions of the advisors and of the students during that period. The population was divides by four catgories, such as: students that had alredy defended their theses, students that had not defended theis thesesm, students that had abandonned the course durind the thesis work, and the category of the advisors. The analysis of the data included questions like: why did the students choose this field of studies, how did they choose theis thesis subjects, the frequency of the counselling sessions, the influence of the advisor on the student, etc. Some aspects of the relationshio were studeid and it was verified that may of may not influence the completion of the thesis and that the main factor success is in reality the determination an motivation of the student.